A Diastereoselective Route to trans‐2‐Aryl‐2, 3‐dihydrobenzofurans through Sequential Cross‐Metathesis/Isomerization/Allylboration Reactions: Synthesis of Bioactive Neolignans. Issue 11 (25th February 2015) - Hemelaere, Rémy; Carreaux, François; Carboni, Bertrand
Abstract: A new highly diastereoselective synthetic route to trans ‐2, 3‐dihydrobenzofuran systems, in particular those bearing an aryl substituent at the C2 position, is described. The cornerstone of our strategy is the implementation of a cross‐metathesis/isomerization/allylboration sequence starting from 2‐allyl‐substituted phenols and aldehydes. After an intramolecular Mitsunobu cyclization step, the anti ‐homoallylic alcohols allow the synthesis of the desired skeleton in a stereoselective fashion. As an illustration, we used this strategy for the preparation of the dihydrodehydrodiconiferyl alcohol (1a ), a natural dihydrobenzofuran neolignan, as well as for a formal synthesis of its O ‐demethylated derivative1b . An enantioselective version of this approach employing a chiral phosphoric acid in the allylboration step is also studied. Abstract : The development of a highly diastereoselective synthesis of trans ‐2, 3‐dihydrobenzofurans based on a cross‐metathesis/isomerization/allylboration sequence is reported. This new approach was efficiently employed for the preparation of natural neolignans.